Nutritional management of very low birth weight at a hospital center of Antananarivo - Ranosiarisoa, Zoly Nantenaina; Ramananirina, Mirana Zita; Tsifiregna, Rosa Lalao; Ravelomanana, Lovaniaina; Ravelomanana, Noëline (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Very low birth weight (VLBW) new-borns represent vulnerable group. The lower the birth weight, the higher the mortality rate. The objective of this study was to describe the nutritional management of VLBW new-borns and to determine their hospital outcome. Methods: A retrospective cohort study was carried out during 24 months in a hospital center of Antananarivo. All newborns weighing less than 1500 g at birth and admitted to neonatal resuscitation service were included. Results: Of the 577 newborns admitted during this period, 48 were retained as very low birth weight. All had less than to 37 gestational age. New-borns less than or equal to 32 gestational age had a 4.02-fold risk of dying. VLBW with a birth weight less than 1,000 g were 2.12 times more likely to die than those between 1,000 and 1,499 g. The use of artificial milk was neither associated with the onset of digestive intolerance nor associated with VLBW early outcome. Conclusions: Hospital nutritional management of VLBW requires specific and delicate care. Breast milk is ideal for the newborn. But if it is not available immediately, the alternative that is not disadvantageous is artificial milk.